2008
DOI: 10.1055/s-0030-1247823
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Anterior Cruciate Ligament Reconstruction Rehabilitation –Part II: Open Versus Closed Kinetic Chain Exercises, Neuromuscular Electrical Stimulation, Accelerated Rehabilitation, and Miscellaneous Topics

Abstract: Anterior cruciate ligament (ACL) reconstruction is a common surgical knee procedure that requires intensive postoperative rehabilitation by the patient. A variety of randomized controlled trials have investigated aspects of ACL reconstruction rehabilitation. A systematic review of English language level 1 and 2 studies identified 54 appropriate randomized controlled trials of ACL rehabilitation. This part of the article discusses open versus closed kinetic chain exercises, neuromuscular electrical stimulation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(127 citation statements)
references
References 33 publications
1
117
0
9
Order By: Relevance
“…Patients with concomitant knee surgical procedures are often delayed in the recovery of knee flexion motion. In a systematic review by Wright et al [16], they found no substantial advantage for the use of a continuous passive motion device in the early post-operative phase based on six randomized controlled trials.…”
Section: Early Post-operative Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with concomitant knee surgical procedures are often delayed in the recovery of knee flexion motion. In a systematic review by Wright et al [16], they found no substantial advantage for the use of a continuous passive motion device in the early post-operative phase based on six randomized controlled trials.…”
Section: Early Post-operative Complicationsmentioning
confidence: 99%
“…Stimulation can be performed in full knee extension for patients with bone-patella-bone grafts and at 60°isometrically for patients with allografts or hamstring autografts. NMES is recommended to be applied at a high-intensity for it to be successful in improving quadriceps strength [16].…”
Section: Early Post-operative Complicationsmentioning
confidence: 99%
“…Although the prior systematic reviews identified a paucity of studies on accelerated rehabilitation 1 , Beynnon et al demonstrated that it is unlikely to be harmful 5 . Recently, numerous additional randomized clinical trials have evaluated the timing and safety of strengthening in accelerated compared with standard rehabilitation (Table III) 6-11 .…”
Section: Postoperative Bracingmentioning
confidence: 99%
“…Four studies included in the previous systematic reviews had evaluated home-based compared with outpatient physical therapy for rehabilitation after ACL reconstruction 1,2 . Despite flaws in reporting and study design that resulted in biases, the studies indicated that a motivated patient could obtain reasonable results with minimally supervised home-based rehabilitation.…”
Section: Home-based Rehabilitationmentioning
confidence: 99%
“…In general, these programs are designed to maximize function by restoring range of motion (ROM), strength, and neuromuscular coordination, (5,6) and typically commence during the acute in-patient period. Early rehabilitation objectives include restoration of knee ROM, pain management, reduction of swelling, early ambulation, and initial recovery of muscle strength.…”
Section: Introductionmentioning
confidence: 99%